And I think to myself what a wonderful world: In search of Louis Armstrong's Brussels collage. (22nd January 2018) - Heyman, Matthias
Abstract : Unknown to many audiences, Louis Armstrong was a skilful bricoleur of collages, using the cardboard boxes of Ampex magnetic tape as his preferred canvas. Among his many collages, now held at the Louis Armstrong Archives in New York's Queens College, there is one that is based on a visual representation of Brussels, the capital of Belgium, the small West-European nation bordering France, the Netherlands, Germany, the Grand Duchy of Luxemburg, and, across the English Channel, the United Kingdom. Upon first sight, it is just another collage dedicated to a concert location, but a closer look reveals it is a rather remarkable piece of art. Not only is it one of Armstrong's most surreal collages, it also comprises not a single visual reference to Brussels or Belgium. A 1958 collage depicting Paris clearly shows the lower half of the Eiffel Tower, but the Brussels collage has no trace of the Atomium, Manneken Pis, beer, waffles, chocolate, or anything else that can be understood as typically Belgian. Instead we see cut-outs of nude women, a number of helmeted men staring into the yonder, and a vulture who seems to be attacking one of the men. The only thing which reveals that the collage is indeed referring to Brussels is its title at the bottom, in Armstrong's hand: 'BRUSSELLS BELGIUM' [sic]. What went on in the trumpeter's mind when he created this mysterious piece? How did his (possible) visit to Brussels trigger him into releasing an aggressive vulture onto his spectators? This article offers a reconstruction of the unfinished quest into the secrets behind this enigmatic collage.